Linking Chromosomal Silencing With Xist Expression From Autosomal Integrated Transgenes - Naciri, Ikrame; Lin, Benjamin; Webb, Chiu-Ho; Jiang, Shan; Carmona, Sarah; Liu, Wenzhu; Mortazavi, Ali; Sun, Sha (Frontiers in Cell and Developmental Biology, 2021)
Xist is the master regulator of X-Chromosome Inactivation (XCI), the mammalian dosage compensation mechanism that silences one of the two X chromosomes in a female cell. XCI is established during early embryonic development. Xist transgene (Tg) integrated into an autosome can induce transcriptional silencing of flanking genes; however, the effect and mechanism of Xist RNA on autosomal sequence silencing remain elusive. In this study, we investigate an autosomal integration of Xist Tg that is compatible with mouse viability but causes male sterility in homozygous transgenic mice. We observed ectopic Xist expression in the transgenic male cells along with a transcriptional reduction of genes clustered in four segments on the mouse chromosome 1 (Chr 1). RNA/DNA Fluorescent in situ Hybridization (FISH) and chromosome painting confirmed that Xist Tg is associated with chromosome 1. To determine the spreading mechanism of autosomal silencing induced by Xist Tg on Chr 1, we analyzed the positions of the transcriptionally repressed chromosomal sequences relative to the Xist Tg location inside the cell nucleus. Our results show that the transcriptionally repressed chromosomal segments are closely proximal to Xist Tg in the three-dimensional nucleus space. Our findings therefore support a model that Xist directs and maintains long-range transcriptional silencing facilitated by the three-dimensional chromosome organization.